2021
DOI: 10.1002/pros.24234
|View full text |Cite
|
Sign up to set email alerts
|

Tissue cholesterol metabolism and prostate cancer aggressiveness: Ethno‐geographic variations

Abstract: Background: Prostate cancer (PCa) is more frequent and more aggressive in populations of African descent than in Caucasians. Since the fatty acid composition of peri-prostatic adipose tissue (PPAT) has been shown to differ according to the ethno-geographic origin and is involved in PCa aggressiveness, we aimed to analyze the cholesterol content of PPAT from Caucasian and African-Caribbean patients, in correlation with markers of disease aggressiveness and cholesterol metabolism in cancer tissues. Methods:The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Through EMT, epithelial cancer cells lose cell polarity and cell–cell adhesion ability, acquire mesenchymal characteristics, and transition from quiescent to malignant forms, which correlate positively with various cancer features, such as migration, invasion, and metastatic potential 24,37 . A previous study revealed that SREBP2 promotes invasion and migration of prostate cancer cells via EMT 38 . Therefore, we speculated that SREBP2 exerts its effects in HCC via EMT.…”
Section: Discussionmentioning
confidence: 93%
“…Through EMT, epithelial cancer cells lose cell polarity and cell–cell adhesion ability, acquire mesenchymal characteristics, and transition from quiescent to malignant forms, which correlate positively with various cancer features, such as migration, invasion, and metastatic potential 24,37 . A previous study revealed that SREBP2 promotes invasion and migration of prostate cancer cells via EMT 38 . Therefore, we speculated that SREBP2 exerts its effects in HCC via EMT.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, PPARγ derived PCa growth and metastasis by upregulating AKT3 could increase mitochondrial biogenesis levels [ 59 ]. Studies have found that the amount of cholesterol is higher in PCa cells compared to normal cells, influencing cancer development and progression [ 60 ]. Henrich et al [ 61 ] revealed that reducing cholesterol in bone marrow myeloid cells can render the transduction of PCa extracellular vesicle signaling, thus hindering the bone metastasis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…To gather a more refined chemical description of cellular states we focus on the lipid fingerprint region and conduct further ATR‐FTIR spectroscopy analysis of lipid extracts of TGF‐β treated cells. Emerging studies linking lipid metabolism with EMT serves as an additional motivation 39–41 …”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies linking lipid metabolism with EMT serves as an additional motivation. [39][40][41] Structural parameters such as saturation, unsaturation, and acyl chain length of fatty acids are estimated from the FTIR spectral peaks at and around 3010, 2954, 2931, 2920, 2870, and 2852 cm −1 which appear consistently in all four samples. Elevated unsaturation index in the treated cells presumably reflects the increased membrane fluidity associated with mesenchymal transition, 42 while decreased acyl chain length is suggestive of an elevated β-oxidation of fatty acids due to a low rate of glycolysis and limited availability of acetyl-CoA characteristic of prostate cancer.…”
Section: Classification Of Pc3 Cells Based On Biochemical and Metabol...mentioning
confidence: 99%